Improving Quality of Patient Data for Treatment of Multidrug- or Rifampin-Resistant Tuberculosis - Campbell, Jonathon R.; Falzon, Dennis; Mirzayev, Fuad; Jaramillo, Ernesto; Migliori, Giovanni Battista; Mitnick, Carole D.; Ndjeka, Norbert; Menzies, Dick (Emerging infectious diseases, 2020)
International policy for treatment of multidrug- and rifampin-resistant tuberculosis (MDR/RR TB) relies largely on individual patient data (IPD) from observational studies of patients treated under routine conditions. We prepared guidance on which data to collect and what measures could improve consistency and utility for future evidence-based recommendations. We highlight critical stages in data collection at which improvements to uniformity, accuracy, and completeness could add value to IPD quality. Through a repetitive development process, we suggest essential patient- and treatment-related characteristics that should be collected by prospective contributors of observational IPD in MDR/RR TB.